PERIORBITAL NECROBIOTIC XANTHOGRANULOMA WITHOUT PARAPROTEINEMIA - Taeko Nakamura-Wakatsuki; Toshiyuki Yamamoto (Our Dermatology Online, 2013)
Introduction: Necrobiotic xanthogranuloma (NXG) is a rare histiocytic disease which most frequently involves periorbital areas. NXG is associated with paraproteinemia with a ratio over 80%. However, a few cases of NXG without paraproteinemia (isolated NXG) have also been reported. Main observation: A 58-year-old Japanese woman complained about asymptomatic dermal nodules on the bilateral lower eyelids. The histopathological examination revealed granulomatous inflammation. Paraproteinemia was not detected either in the serum or in the urine. The size of the nodules has been constant, and she has been under careful follow-up without any systemic therapies. Conclusions: NXG is frequently associated with paraproteinemia, which may develop later. Patients with NXG need careful follow-up including repeated blood tests.